2021
DOI: 10.1055/s-0041-1732431
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Disparities in Thrombotic and Bleeding Diatheses Revisited: A Systematic Review of Microsurgical Breast Reconstruction across the East and West

Abstract: Background Ethnicity has been shown to play a role in disparate coagulative responses between East Asian and Caucasian patients undergoing nonmicrovascular surgery. In this study, we sought to further investigate this hematologic phenomenon between the two ethnic groups within the field of microsurgical breast reconstruction. Methods A systematic review examining the reported incidence of microvascular thrombosis and all-site bleeding among breast free flaps in East Asians and Westerners was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…crosurgical breast reconstruction. That study reported a significantly higher rate of bleeding events in Asian patients than in Western patients (2.6% vs. 1.2%, P = 0.002) [37]. These findings further augment the emerging body of evidence suggesting possible differences in the coagulative responses between Asian and Western populations [33,37].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…crosurgical breast reconstruction. That study reported a significantly higher rate of bleeding events in Asian patients than in Western patients (2.6% vs. 1.2%, P = 0.002) [37]. These findings further augment the emerging body of evidence suggesting possible differences in the coagulative responses between Asian and Western populations [33,37].…”
Section: Discussionmentioning
confidence: 54%
“…That study reported a significantly higher rate of bleeding events in Asian patients than in Western patients (2.6% vs. 1.2%, P = 0.002) [37]. These findings further augment the emerging body of evidence suggesting possible differences in the coagulative responses between Asian and Western populations [33,37]. As such, the introduction of PTP in this population group should be a calculated decision, one that takes into account the intrinsic differences in hemostatic pathways that result in a lower incidence of VTE events and conversely, higher bleeding risks.…”
Section: Discussionmentioning
confidence: 84%
“…A systematic review comparing the East Asian population to the Western population found that Westerners were more susceptible to microvascular thrombosis while Eastern Asians were at increased risk of all site bleeding during breast free flap reconstruction. 25 These findings suggest clinically significant differences in the rate of thrombosis, as well as the propensity to inordinately bleed among different ethnic populations, both of which can significantly increase morbidity and mortality among microvascular surgery patients. Further research is necessary to elucidate links between unique genetic polymorphisms and hypercoagulable states within homogenous racial groups.…”
Section: Discussionmentioning
confidence: 91%
“…Such circumstances disparate coagulative responses and potential susceptibility to pharmacologic intervention. 52 53 The authors are also aware that ischemia-reperfusions injuries under which microcapillary venous flap thrombosis typically occurs differ from the model that is presented. In addition, this study includes mostly semiquantitative analysis and lacks data on tissue oxygen tension, perfusate samples, and histologic evaluation.…”
Section: Discussionmentioning
confidence: 99%